2021
DOI: 10.3390/children8020158
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Views and Experiences of Treatment Adherence and Parent/Child Co-Management in Eczema: A Qualitative Study

Abstract: Eczema affects one in five children and can have a substantial impact on quality of life. This qualitative study aimed to explore children’s views and experiences of eczema and what may affect treatment adherence from their perspective. We conducted semi-structured, face-to-face interviews with children with eczema aged 6–12 years from March to July 2018. Interviews were transcribed verbatim and analysed using inductive thematic analysis. We found that children do not typically view eczema as a long-term condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 44 publications
0
19
0
2
Order By: Relevance
“…26 These findings are consistent with previous qualitative research, which identifies trade-offs between effectiveness and acceptability when choosing an emollient. 27,28 In short, a one size fits all approach is not appropriate and users need to be able to choose from a range of emollient types to suit their needs and preferences. Interpretation of our findings will be strengthened by a planned formal health economic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…26 These findings are consistent with previous qualitative research, which identifies trade-offs between effectiveness and acceptability when choosing an emollient. 27,28 In short, a one size fits all approach is not appropriate and users need to be able to choose from a range of emollient types to suit their needs and preferences. Interpretation of our findings will be strengthened by a planned formal health economic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…found treatment adherence could be supported by stressing that AD is a long‐term episodic condition. 21 The perception that AD is not considered as a long‐term condition by parents of children with AD is also highlighted by the review of qualitative studies of Teasdale et al. This had implications for the perceived necessity of long‐term treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The reported improvements to routine and increased use of treatments due to the removal of barriers to eczema self‐management during periods of staying at home highlight the hidden burden of self‐managing eczema and the importance of environmental factors. 17 , 18 , 19 There is a need for high quality consistent information and advice about eczema. 18 , 20 , 21 Eczema has a considerable psychosocial impact, 18 , 22 particularly amongst young people, 23 and families of children with eczema often need to rely on others for support with eczema care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified barriers to self‐management, including limited knowledge of eczema, concerns about eczema treatments and treatments being time‐consuming. 3 , 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%